Electromyographic comparison of the back sqaut and overhead squat - Swinton, P. A.; Aspe, R.; Keogh, J. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The present study sought to compare the electrical activity of core and lower-body muscles during performance of the back squat and overhead squat. Fourteen male rugby union athletes performed repetitions of both squatting movements with 60, 75 and 90% of their respective 3RM loads. Additional comparisons were made with isolation exercises designed to target the core musculature and a further condition to equate the absolute load lifted. The overhead squat resulted in slight increases in activity of the rectus abdominus and external oblique, with larger decreases in activity of the erector spinae and lower-body muscles. The results show that the differences in muscle activity are largely a function of the absolute load lifted and that anterior core muscles are recruited to a greater extent during isolation exercises compared with squatting movements.